Blood pressure and hypertension in older adults with a history of regular cannabis use: findings from the Multi-Ethnic Study of Atherosclerosis - Corroon, Jamie; Bradley, Ryan; Allison, Matthew A.; Grant, Igor (Frontiers in Cardiovascular Medicine, 2024)
Background: Observational evidence investigating associations between cannabis use and blood pressure and hypertension is inconsistent.Methods: Cross-sectional data from 3,255 participants at Exam 6 (2016-2018) of the Multi-Ethnic Study of Atherosclerosis (MESA) were analyzed, including self-reported cannabis smoking patterns, standardized measures of systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP; BP collectively), and hypertension. ANCOVA and multivariable relative risk regression models were used to calculate adjusted means for BP and adjusted prevalence ratios (PRs) for prevalent hypertension.In fully adjusted ANCOVA models, a history of regular cannabis smoking, when compared to no history, was not significantly associated with increased SBP (mean difference: -0.1 mmHg (95% CI: -3.0 to 2.7)), DBP (mean difference: 0.5 mmHg (95% CI: -0.9 to 1.9)), PP (mean difference: -0.5 mmHg (95% CI: -2.7 to 1.7)), or prevalent hypertension (PR: 1.04 (95% CI: 0.97 to 1.11)). Furthermore, no associations were observed for either the duration or recency (in the past month) of cannabis smoking or number of joint/pipe years. Models exploring potential interactions between a history of regular cannabis smoking and age, sex, race/ethnicity, and cigarette smoking status were not significant for either BP or hypertension.In a cohort of racially and ethnically diverse older adults with a high prevalence of hypertension, no evidence of increased risk due to regular cannabis smoking was found for either the blood pressure or hypertension.